2021
DOI: 10.3390/agronomy11122511
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine Ammonia-Lyase (PAL) Genes Family in Wheat (Triticum aestivum L.): Genome-Wide Characterization and Expression Profiling

Abstract: Phenylalanine ammonia-lyase (PAL) is the first enzyme in the phenylpropanoid pathway and plays a vital role in adoption, growth, and development in plants but in wheat its characterization is still not very clear. Here, we report a genome-wide identification of TaPAL genes and analysis of their transcriptional expression, duplication, and phylogeny in wheat. A total of 37 TaPAL genes that cluster into three subfamilies have been identified based on phylogenetic analysis. These TaPAL genes are distributed on 1A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 88 publications
(127 reference statements)
1
24
0
1
Order By: Relevance
“…Studies have shown that, compared with drought-sensitive genotypes, the expression levels of PAL genes in the wheat root of drought-resistant genotypes are higher. Still, the expression levels of five PAL genes are deficient [ 49 ]. After drought stress, 70% of CsPALs in cucumber seedlings showed a trend of increasing and decreasing, but the overall expression level was up-regulated [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that, compared with drought-sensitive genotypes, the expression levels of PAL genes in the wheat root of drought-resistant genotypes are higher. Still, the expression levels of five PAL genes are deficient [ 49 ]. After drought stress, 70% of CsPALs in cucumber seedlings showed a trend of increasing and decreasing, but the overall expression level was up-regulated [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dissimilarities were calculated by calculating Euclidean distance and applying Ward’s method. Heatmaps were constructed using R package pheatmap (version 1.7) ( Kolde and Kolde, 2015 , Rasool et al, 2021 ). For the estimation of broad sense heritability (H), data was subjected to ANOVA and then the total variances were subdivided into its parts.…”
Section: Methodsmentioning
confidence: 99%
“…The protein sequences of Triticum aestivum PPR, OZ1, and Multiple organellar RNA editing factor (MORF)/ RIP were obtained from the Ensembl database [34]. The procedure reported in our previous work was employed for transcriptome analysis [35]. In details, total RNA from root samples of wheat genotypes was extracted using Gene JET™ Plant RNA Purification Mini Kit (Catalog # K0801).…”
Section: Expression Analyses Of Rna Editing Gene Familiesmentioning
confidence: 99%